Kingdom of the Netherlands-Aruba : Staff Report for the 2001 Article IV Consultation Discussions. (IMF Staff Country Reports; Country Report, 2001)
The government's plans to reform the tax system and administration are well founded. The Central Bank of Aruba is to be commended for its prudent management of monetary policy, as demonstrated by the continued credibility and strength of the peg to the U.S. dollar, buttressed by a robust foreign reserve position. There has been significant progress in expanding and strengthening the supervisory and regulatory framework of financial activities. Renewed initiatives on structural reforms will improve efficiency in the use of resources and attract strategic investment.